Employment Protection Legislation and Labor Markets in Transition : Assessing the Effects of the Labor Code in Armenia - Hartwell, Christopher A. (2012)
The effects of employment protection legislation (EPL) on a country's labor market are clear in theory but empirical evidence is only starting to catch up. In particular, EPL is not robust as an indicator of overall unemployment, but previous panel data analyses have shown it affects the flow of workers into and out of employment. Examining monthly and quarterly data from Armenia, I find that the country's package of EPL has this same effect, and worker flows have slowed under the country's new Labor Code. The paradox of where Armenia's workforce is going still remains but can be hypothesized as entering the informal sector.